Respuesta :
Answer:
[tex](-3,-12)[/tex]
[tex]x=-3, y=-12[/tex]
Step-by-step explanation:
So we have the system:
[tex]3x+y=-21\\y=4x[/tex]
To solve this, we can do some substitution. Substitute the y in the first equation for the 4x in the second:
[tex]3x+y=-21\\3x+(4x)=-21[/tex]
Combine like terms:
[tex]7x=-21[/tex]
Divide both sides by 7. The left side cancels:
[tex](7x)/7=(-21)/7\\x=-3[/tex]
So we determined that x is -3. Now, plug this number back into the second equation:
[tex]y=4x\\y=4(-3)=-12[/tex]
So the solution is:
[tex](-3,-12)[/tex]
Answer:
[tex]\Large \boxed{x=-3 \ } \\ \\ \Large \boxed{y=-12}[/tex]
Step-by-step explanation:
3x + y = -21
y = 4x
Substitue y = 4x in the first equation.
3x + 4x = -21
Combine like terms.
7x = -21
Divide both sides by 7.
x = -3
Let x = -3 for the second equation.
y = 4(-3)
Multiply.
y = -12
The solution for the system of equations is x = -3 and y = -12.